Enhancing the efficiency of government control over agroindustrial sector to maintain food security (Journal of actual problems of jurisprudence, 2018)
The aim of this article is to describe challenges associated with enhancement of government control over agroindustrial sector in order to maintain food security. The necessity for government control over agricultural industry stems from the fact that the State is accountable to its citizens for establishing their standard living conditions, food and other agricultural product supplies. This article explores the concepts, objectives and enhancement techniques for government control over agroindustrial sector, challenges associated with maintaining food security and the ways to address these challenges.Key words: government regulation, agroindustrial sector, food security, legal support, government functions.